"They Haven't Made a Slot for Us Yet": Conceptualizing the Health Care and Social Service Needs of Older Gay Men Living with HIV in Canada. Issue 2 (28th January 2022) - Kia, Hannah; Grace, Daniel; Strike, Carol; Ferlatte, Olivier; Knight, Rod; Salway, Travis; Ross, Lori E.
ABSTRACT: In this paper, we present the findings of a qualitative study aimed at conceptualizing the service needs of aging gay men living with HIV (GMLH). Our analysis is based on interview data from 16 gay-identified men living with HIV, ages 50 and over. Drawing on a framework of intersectionality, which theoretically accounts for interlocking expressions of marginalization in groups affected by multiple systems of oppression, we highlight the practical, social, and mental health needs of this population, as well as services that could be designed or adapted to address these concerns. We also emphasize the relevance of specialized training for caring professionals serving older GMLH, and articulate the need for initiatives that more fully engage gay men aging with HIV in the development and delivery of services intended for their use.